Social Media Practices of Small and Medium Enterprises in Masbate Province: Impact on Industry Competitiveness - Toling, Rony Saludar (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Small and medium enterprises (SMEs) can benefit significantly from social media due to its user-friendly nature, cost-effectiveness, and widespread accessibility. By leveraging social media platforms, SMEs can effectively communicate with customers, market their products, facilitate internal collaboration, and provide customer sup-port at minimal costs.This research assessed the use of social media among SMEs in the fashion, food, beverages, cosmetics, and clothing industries in Masba-te province to enhance competitiveness. It focused on key areas such as customer engagement, social network marketing, website promo-tion, customer relationship management, and brand management, while also evaluating industry competitiveness based on customer satisfaction, loyalty, operational efficiency, and profitability.A quantitative descriptive approach was employed to evaluate variables and their relationships. Employees from SMEs were ran-domly selected as respondents, while industry customers were cho-sen through purposive sampling. A self-designed Likert-scale survey captured respondents' perspectives on the impact of social media practices on industry competitiveness, combining both quantitative and qualitative insights.The analysis included descriptive statistics, such as percentages and frequencies, to outline respondent profiles, and means and stand-ard deviations to examine trends in social media practices among SMEs. Pearson correlation analysis was conducted to assess the effec-tiveness of these practices, while a t-test was used to highlight differ-ences in perceptions between respondent groups regarding social media effectiveness and industry competitiveness.